2020
DOI: 10.1007/s12217-020-09799-8
|View full text |Cite
|
Sign up to set email alerts
|

Influence of an External Perpendicular Oscillation on Stability of a Vertical Falling Liquid Film

Abstract: A vertical falling Newtonian liquid film flow is inherently unstable to surficial long-wave disturbances. Imposing external oscillation can stabilize the long-wave instability, but also triggers additional parametric instabilities. The effect of oscillation frequency on the stability is subtle. By using the “viscosity-gravity” scaling, the effect of oscillation frequency on the stability can be investigated exhaustively by separating it from other control parameters. In this paper, the effects of external perp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
(8 reference statements)
0
1
0
Order By: Relevance
“…27,28 Kliakhandler et al 29 observed three typical flow regimes that increase with velocity: the isolated droplet regime, the Rayley-Plateau regime, and the convective regime. Additionally, many authors have worked on the coating flow of vertical cylindrical fibers in more complex situations, such as radial electric fields, 30 conductive liquid films, 31 applying external oscillations, 32 heating fibers, 33 and rotating fibers. 34 Pan et al 35 found that the volume of retained droplets on curved fibers is three times larger than that on horizontal fibers, and the optimal angle is about 36 .…”
mentioning
confidence: 99%
“…27,28 Kliakhandler et al 29 observed three typical flow regimes that increase with velocity: the isolated droplet regime, the Rayley-Plateau regime, and the convective regime. Additionally, many authors have worked on the coating flow of vertical cylindrical fibers in more complex situations, such as radial electric fields, 30 conductive liquid films, 31 applying external oscillations, 32 heating fibers, 33 and rotating fibers. 34 Pan et al 35 found that the volume of retained droplets on curved fibers is three times larger than that on horizontal fibers, and the optimal angle is about 36 .…”
mentioning
confidence: 99%